Microevolution of pandemic Vibrio parahaemolyticus assessed by the number of repeat units in short sequence tandem repeat regions. - Katherine García; Ronnie G Gavilán; Manfred G Höfle; Jaime Martínez-Urtaza; Romilio T Espejo (PLoS ONE, 2012)
The emergence of the pandemic strain Vibrio parahaemolyticus O3:K6 in 1996 caused a large increase of diarrhea outbreaks related to seafood consumption in Southeast Asia, and later worldwide. Isolates of this strain constitutes a clonal complex, and their effectual differentiation is possible by comparison of their variable number tandem repeats (VNTRs). The differentiation of the isolates by the differences in VNTRs will allow inferring the population dynamics and microevolution of this strain but this requires knowing the rate and mechanism of VNTRs' variation. Our study of mutants obtained after serial cultivation of clones showed that mutation rates of the six VNTRs examined are on the order of 10(-4) mutant per generation and that difference increases by stepwise addition of single mutations. The single stepwise mutation (SSM) was deduced because mutants with 1, 2, 3, or more repeat unit deletions or insertions follow a geometric distribution. Plausible phylogenetic trees are obtained when, according to SSM, the genetic distance between clusters with different number of repeats is assessed by the absolute differences in repeats. Using this approach, mutants originated from different isolates of pandemic V. parahaemolyticus after serial cultivation are clustered with their parental isolates. Additionally, isolates of pandemic V. parahaemolyticus from Southeast Asia, Tokyo, and northern and southern Chile are clustered according their geographical origin. The deepest split in these four populations is observed between the Tokyo and southern Chile populations. We conclude that proper phylogenetic relations and successful tracing of pandemic V. parahaemolyticus requires measuring the differences between isolates by the absolute number of repeats in the VNTRs considered.